Strategies to attenuate maladaptive inflammatory response associated with cardiopulmonary bypass - Banerjee, Debolina; Feng, Jun; Sellke, Frank W. (Frontiers in Surgery, 2024)
Cardiopulmonary bypass (CPB) initiates an intense inflammatory response due to various factors: conversion from pulsatile to laminar flow, cold cardioplegia, surgical trauma, endotoxemia, ischemia-reperfusion injury, oxidative stress, hypothermia, and contact activation of cells by the extracorporeal circuit. Redundant and overlapping inflammatory cascades amplify the initial response to produce a systemic inflammatory response, heightened by coincident activation of coagulation and fibrinolytic pathways. When unchecked, this inflammatory response can become maladaptive and lead to serious postoperative complications. Concerted research efforts have been made to identify technical refinements and pharmacologic interventions that appropriately attenuate the inflammatory response and ultimately translate to improved clinical outcomes. Surface modification of the extracorporeal circuit to increase biocompatibility, miniaturized circuits with sheer resistance, filtration techniques, and minimally invasive approaches have improved clinical outcomes in specific populations. Pharmacologic adjuncts, including aprotinin, steroids, monoclonal antibodies, and free radical scavengers, show real promise. A multimodal approach incorporating technical, circuit-specific, and pharmacologic strategies will likely yield maximal clinical benefit.